PENERAPAN MEDIA SICA BOX UNTUK MENINGKATKAN HASIL BELAJAR IPAS PADA KONSEP SIFAT-SIFAT CAHAYA DI KELAS V SDN BRUMBUNGAN LOR - Azizah Tun Nafsiyah; Ribut Prastiwi Sriwijayanti; Ani Anjarwati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Low learning outcomes in the cognitive domain of students are still one of the problems that are often found in every school. One of them is the elementary school that the researcher made the research site. It was found that there are factors that cause low student scores, namely the lack of teachers in using learning media during the teaching and learning process. The purpose of this study was to improve student learning outcomes on the concept of “Properties of Light” Class V at SDN Brumbungan Lor, Probolinggo Regency by using learning media, namely Sica Box media. This research uses the Classroom Action Research (PTK) method. This research has II cycles and there are four phases of activity in one cycle. The findings of this research show an increase in the learning achievements of students. Referring to the initial test results, the number of students who have not reached mastery is 10 (52.63%) and those who reach mastery are 9 (47.36%).In the first cycle, 13 students (68.42%) were recorded as complete. Then, in the second cycle there were 18 students (94.73%) who were complete, and 1 student (5.26%) was not complete. Therefore, based on these outcomes, it can be concluded that the Sica Box media can boost the learning achievement of fifth grade students at SD Negeri Brumbungan Lor.